2013
DOI: 10.2319/122612-968.1
|View full text |Cite
|
Sign up to set email alerts
|

Corticotomy-assisted molar protraction with the aid of temporary anchorage device

Abstract: This case report describes the interdisciplinary management of a 58-year-old woman who was missing lower first molars and supraerupted maxillary first molars. The treatment plan included intrusion of the upper first molars and corticotomy-assisted mandibular second molar protraction with the aid of temporary anchorage devices. Miniscrews were effective in intrusion of the maxillary first molars and protraction of the lower second molars. Although good functional outcome was achieved in 41 months, the corticoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
2
18
1
1
Order By: Relevance
“…41,42 The 21 day treatment period was chosen because it represented the time of maximum RAP response in rats according to Yaffe et al and has since been used in other studies examining RAP-based ATM in rats. 4345 Even so, future studies should consider additional time points to examine long-term effects and further studies are required to establish the number and frequency of MOPs to optimally induce ATM and maximally reduce treatment duration in clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The 21 day treatment period was chosen because it represented the time of maximum RAP response in rats according to Yaffe et al and has since been used in other studies examining RAP-based ATM in rats. 4345 Even so, future studies should consider additional time points to examine long-term effects and further studies are required to establish the number and frequency of MOPs to optimally induce ATM and maximally reduce treatment duration in clinical cases.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Although scientific controversy persists on whether it is possible to move the teeth efficiently through the constricted alveolar ridge to close space, clinical consensus exists that the periodontal risks of bony dehiscence and further attachment loss will be increased around the moved teeth. 5,6 An interesting orthodontic trial designed to overcome this limitation found coronal increments of bone height on the preexisting atrophic ridge by well-controlled bodily tooth movement toward the ridge. 7 Instead of marginal bone resorption by compression on the side toward which a tooth crown was tipped, root dominant movement induced coronal bone apposition even on the side ahead of the moving root, which was interpreted as being related to the piezoelectric effect of bone-bending theory.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Although corticotomy assisted molar protraction is a possibility, limited duration of the corticotomy effect on the rate of tooth movement, if considered within the context of a prolonged treatment time observed with molar protractions appears to be unjustified. [ 18 ] Molar protraction needs high anchorage, and tipping of the molars and root resorption can happen if anchorage is inadequate. [ 19 ] Molar protraction with the help of TAD controls anchorage loss which is frequently used in molar protraction cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 24 ] We did not experience any kind of miniscrew failure, breakage, or patient discomfort in this case. The primary biological factors that determine miniscrew stability are bone density (or bone quality),[ 23 ] peri-implant soft-tissue health,[ 18 ] adequacy of peri-implant bone stock, and operator technique. [ 25 ] Screws placed through the nonkeratinized gingiva or movable gingiva stimulate the surrounding soft tissue and sometimes evoke the peri-implantitis,[ 26 ] which we have avoided.…”
Section: Discussionmentioning
confidence: 99%